Exploring children’s symbolic play preferences: Promoting autonomy and well-being in early childhood education - Charalampous, Afroditi; Sidiropoulou, Tryfeni; Vlachou, Sofia (American Journal of Education and Learning, 2025)
Symbolic play plays an important role in a child’s life. Using costumes, objects, or even without any materials, children take on real or imaginary roles, experiment, express themselves, and explore the adult world. Everything in their environment "comes to life," creating an imaginary world where princesses, action heroes, and jungle animals take center stage. The present study investigates the preferences of children, aged 3 to 6 years old, in symbolic play using disguise materials in a private Early Childhood Education and Care setting. The aim is to capture their choices regarding the roles they choose to play, either in free activity or in adult-led activity, and whether these preferences change as they grow older. The outcomes showed that as children get older, they are influenced by the media movies, cartoons, advertisements which results in diminishing their imagination. Children at all ages seem to pick costumes that personify their gender roles. Moreover, it seems that adults indirectly guide their children to certain preferences based on gender and current fashion. Consequently, it is important that the children’s voices be heard and taken into consideration by the adults surrounding them parents and educators and this ensures the well-being of children regardless of gender. The adults around them parents and educators should follow a pedagogical approach oriented towards the recognition of children’s rights, which allows and reinforces them to participate and act independently.